2013
DOI: 10.4236/ns.2013.51010
|View full text |Cite
|
Sign up to set email alerts
|

Isotope effects of plasma chemical carbon oxidation in a magnetic field

Abstract: The influence of different factors on the plasma chemical reactions is widely studied today. However, insufficient consideration is given to the research of paramagnetic phenomena which takes place in plasma systems. The results of modeling the process of redistribution carbon isotopes between different phases while oxidizing it in high-frequency low-temperature plasma in an external magnetic field are shown in the article. The equilibrium concentrations of components involved in the oxidation process in a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…External magnetic field leads to ordering the spin spatial orientations of the radical unpaired electrons and Larmor's precession around the magnetic field lines. Precession changes the number of possible combinations of spin spatial orientations of the colliding atom valence electrons significantly [15]. Therefore external magnetic field significantly influences the chemical reaction conditions and the certain compounds formation.…”
Section: Spin Mechanism Of the Isotope Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…External magnetic field leads to ordering the spin spatial orientations of the radical unpaired electrons and Larmor's precession around the magnetic field lines. Precession changes the number of possible combinations of spin spatial orientations of the colliding atom valence electrons significantly [15]. Therefore external magnetic field significantly influences the chemical reaction conditions and the certain compounds formation.…”
Section: Spin Mechanism Of the Isotope Separationmentioning
confidence: 99%
“…According to [15] where it was experimentally demonstrated that the increase in 13 C concentration in the reaction products relative to natural content at atmosphere depends on the distance between the magnetic field application domain and the end of the high-voltage electrode. The 13 C isotope content in gaseous products of plasma-chemical reactions was studied according to the external magnetic field (1.2 T) location relate to the plasma torch (Figure 3).…”
Section: Spin Mechanism Of the Isotope Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Radical processes in low-temperature plasma differ from those in fluid in an external constant magnetic field. The magnetic field has a significant effect on plasma processes and the formation rate of various compounds containing different isotopes [4]. The simulation of plasma-chemical processes requires taking into account not only the kinetics of chemical reactions, which considers the collision frequency and distribution of reagents for the excited states, but also the spin phenomena.…”
Section: Analysis Of Plasma Processesmentioning
confidence: 99%
“…Isotopic composition of carbon monoxide formed during the partial oxidation of carbon plasma in a magnetic field is determined by the following processes [9]:…”
Section: Analysis Of Plasma Processesmentioning
confidence: 99%